PENGARUH METODE KONTRASEPSI, LAMA PENGGUNAAN KONTRASEPSI TERHADAP KEJADIAN HIPERTENSI PADA IBU PASANGAN USIA SUBUR DIPUSKESMAS PULO BRAYAN TAHUN 2020 - Debora Lestari Simamora; Elfalini Warnelis (Jurnal Maternitas Kebidanan, 2021)
Based on data from Puskesmas Pulo Brayan Medan, the number of hypertension sufferers in the last 3 years has increased. In 2018 the number of hypertension sufferers was 378 people, in 2019 there were 384 people, and in 2020 there were 394 people. Of the 394 patients with hypertension, 214 were women of PUS. There are many factors that are thought to be the cause of hypertension in women with PUS, such as the use of contraceptives. The aim of this study was to analyze the effect of duration of use of contraceptives, contraceptive methods, duration of use of contraception, on the incidence of hypertension in women with fertility. This research is an analytical research and is quantitative in nature with a case control design (case control). The research was conducted in the area of ​​Pulo Brayan Health Center, Medan. The study population was 8,547 people and the sample was obtained as many as 166 people who were divided into 2 groups, each 83 people. Data analysis used univariate analysis, bivariate analysis with chi-square. The results showed that the duration of use of contraception, the method of contraception, the duration of use of contraception, had an effect on the incidence of hypertension in PUS mothers in the Pulo Brayan Public Health Center, Medan, p <0.05. The variable with the greatest influence in this study was the variable body mass index (BMI) which had a value of Exp (B) = 20.639 (95% CI = 5.850-72.823). It is recommended to the Head of Puskesmas Pulo Brayan Medan to inform PUS mothers who use hormonal contraceptives such as pills and injections to carry out routine blood pressure checks at the puskesmas so that early detection of other complications that can accompany an increase in blood pressure.